“The Declaration on the Common Language”: A View from the Inside - Bugarski, Ranko (Aegean Working Papers in Ethnographic Linguistics, 2020)
The editor of the special issue of AWPEL on former Yugoslavia has kindly invited me to provide the journal’s readership with more information on this document, evaluated in distinctly negative terms by Professor Christian Voß in his contribution to the present collection of articles. I will gladly do so, in my capacity as a native speaker of Serbo-Croatian, a consultant in the drafting process of the Declaration and one of its initial signatories and public supporters. [...]